Building with bamboo : design and technology of a sustainable architecture - Minke, Gernot (2022)
"Traditionally a building material of the warmer climate zones, bamboo is becoming increasingly popular amongst architects in the northern hemisphere; bamboo has several advantages - it is very stable, of low weight, and highly elastic, in addition to being readily available as well as renewable. The applications of bamboo in architecture have diversified considerably, so that today, even structures with large spans - such as bridges - are built with this material. Renowned universities like the ETH Zurich or the SUTD in Singapore have conducted research on engineered bamboo which will further expand its use. The third edition of this manual provides a systematic overview of the applications and processing methods of this renewable material. Recent inspiring bamboo buildings have been added"--